2018
DOI: 10.1002/art.40544
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Biomarkers for the Occurrence of Uveitis in Juvenile Idiopathic Arthritis

Abstract: ObjectiveTo analyze the prognostic value of demographic, clinical, and therapeutic factors and laboratory biomarkers and to assess their role in predicting uveitis occurrence in patients with juvenile idiopathic arthritis (JIA).MethodsPatients with JIA were enrolled within the first year after JIA diagnosis. Demographic and clinical parameters were documented. Serum samples were collected at study enrollment, at 3‐month follow‐up visits within the first year, and then every 6 months. A multivariable Cox regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 45 publications
1
37
1
Order By: Relevance
“…Elevated ESR appeared as a valid baseline prognostic factor for uveitis occurrence in JIA patients [13, 27, 29, 33, 34]. According to our present data, it did not appear as a useful predictor of the further uveitis course, which is probably influenced by anti-inflammatory treatment instituted for JIA.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Elevated ESR appeared as a valid baseline prognostic factor for uveitis occurrence in JIA patients [13, 27, 29, 33, 34]. According to our present data, it did not appear as a useful predictor of the further uveitis course, which is probably influenced by anti-inflammatory treatment instituted for JIA.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous data disclosed that S100 serum levels in JIAU patients were higher in patients with active uveitis and suggested that they may reflect eye disease [16]. High S100A12 levels in JIA patients were significantly associated with the risk for uveitis [34]. Our presented data show that S100A12 might not be a useful biomarker for monitoring uveitis activity during the course of JIA, probably influenced by the DMARDs being used to treat the underlying rheumatic disease [35].…”
Section: Discussionmentioning
confidence: 69%
“…There is increasing evidence indicating that B and plasma cells, representing the predominant cellular infiltrate, play a crucial role in the disease (1316). This hypothesis is supported by the observation that 80% of JIAU patients are positive for serum anti-nuclear antibodies (ANA), which represent an important risk factor for uveitis occurrence in JIA patients (6, 8). However, the pathogenic contribution of ANA or autoantibodies to JIAU is still largely undefined.…”
Section: Introductionmentioning
confidence: 91%
“…Uveitis in children and adolescents is frequently related to JIA (35), and, vice versa, represents a common extra-articular manifestation of disease (5, 6). JIA-associated uveitis (JIAU) occurs in 9 to 12% of children with JIA and is observed particularly frequently in the oligoarthritis subtype (7, 8).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of chronic inflammation, patients with JIA suffer from joint pain, swelling, restricted range of motion and joint deformity (1). Severe extra-articular abnormalities may also accompany this disease, including uveitis, which occurs more frequently in antinuclear antibody (ANA)-positive patients and can lead to blindness, and macrophage activation syndrome (MAS), a complication of sJIA that can lead to multi-organ insufficiency and even mortality (3,4) Previous studies indicated that vitamin D played an important role in maintaining both the skeletal and immune systems (5,6). Vitamin D regulates the innate and adaptive immune systems by activating the vitamin D receptor, which is distributed widely on immune cells (7,8).…”
Section: Introductionmentioning
confidence: 99%